Imbalance between the anti- and pro-inflammatory milieu in blood leukocytes of autistic children. (February 2017) - Ahmad, Sheikh F.; Nadeem, Ahmed; Ansari, Mushtaq A.; Bakheet, Saleh A.; Attia, Sabry M.; Zoheir, Khairy M.A.; AL-Ayadhi, Laila Yousef; Alzahrani, Mohammad Z.; Alsaad, Abdulaziz M.S.; Alotaibi, Moureq R.; Abd-Allah, Adel R.A.
Highlights: Enhanced pro-inflammatory cytokine production (IL-21/IL-22) on PBMC in AU. Decreased anti-inflammatory molecules (IL-27/CTLA-4) on PBMC in AU. Induction of IL-21/IL-22 protein and mRNA expression in AU children. Decreased IL-27 mRNA expression in children with AU. Abstract: Accumulating evidence suggests an association between immune dysfunction and autism disorders in a significant subset of children. In addition, an imbalance between pro- and anti-inflammatory pathways has been proposed to play an important role in the pathogenesis of several neurodevelopmental disorders including autism; however, the role of anti-inflammatory molecules IL-27 and CTLA-4 and pro-inflammatory cytokines IL-21 and IL-22 has not previously been explored in autistic children. In the current study, we investigated the expression of IL-21, IL-22, IL-27, and CD152 (CTLA-4) following an in-vitro immunological challenge of peripheral blood mononuclear cells (PBMCs) from children with autism (AU) or typically-developing children (TD) with phorbol-12-myristate 13-acetate (PMA) and ionomycin. In our study, cells from children with AU had increased IL-21 and IL-22 and decreased CTLA-4 expression on CD4 + T cells as compared with cells from the TD control. Similarly, AU cells showed decreased IL-27 production by CD14 + cells compared to that of TD control cells. These results were confirmed by real-time PCR and western blot analyses. Our study shows dysregulation of the immune balance in cells from autistic children as depicted by enhanced pro-inflammatory cytokines, 'IL-21/IL-22' and decreased anti-inflammatory molecules, 'IL-27/CTLA-4'. Thus, further study of this immune imbalance in autistic children is warranted in order to facilitate development of biomarkers and therapeutics.